Over 170 years later: redescription of the genus Glyphuchus Stål (Hemiptera: Pentatomidae: Discocephalinae), with the first description of the male - López, Guilherme E. L.; Carrenho, Renan; Schwertner, Cristiano F. (Zootaxa, 2023)
The rare Neotropical Discocephalini (Heteroptera: Pentatomidae) monotypic genus Glyphuchus Stål, 1860 and its type species Glyphuchus sculpturatus Stål, 1860 are known only from the female holotype. Here, they are redescribed based on a recently collected specimen and on the holotype. The male of the genus is described for the first time based on a specimen collected in a protected area of the Atlantic Rain Forest, in southeastern Brazil. General morphology and male and female genitalia are described and compared to those of other Discocephalini genera. Photos of the main morphological characters are presented, as well as photos of the living and preserved specimens. The relevance of protected areas for studies on biodiversity and natural history is highlighted.